PENGARUH METODE DEMONSTRASI TERHADAP MOTIVASI BELAJAR FIQIH SISWA KELAS VII MTs NW SURALAGA TAHUN PELAJARAN 2024/2025 - Lathif, Muhammad Abdul; Haryadi, L. Fauzi; Arifin, Zainul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is motivated by the low learning motivation of students in fiqh lessons, which is caused by the use of conventional teaching methods such as lectures and question-and-answer sessions. This leads to a lack of student engagement in the learning process, resulting in limited understanding of fiqh material. Therefore, an alternative teaching method that is more engaging and interactive is needed, one of which is the demonstration method. The purpose of this study is to determine the effect of the demonstration method on the learning motivation of seventh-grade students in fiqh subjects at MTs NW Suralaga in the 2024/2025 academic year. This research employs a quantitative approach with a quasi experimental design using a post-test only control group. The sampling technique used is probability sampling, specifically Simple Random Sampling. The subjects in this study were seventh-grade students at MTs NW Suralaga, consisting of two classes: class VII A as the experimental group (22 students) The results showed that the demonstration method had a significant effect on students' motivation to learn fiqh. This was evidenced by the hypothesis testing, which showed a significance value of 0.042 (< 0.05), indicating that the alternative hypothesis (Ha) is accepted. Students taught using the demonstration method had a higher level of learning motivation compared to those taught using conventional methods. It can be concluded that the demonstration method is effective in increasing students' motivation to learn fiqh. This method is suitable for application in fiqh learning to create an active, enjoyable, and meaningful learning environment